Fundamental Mechanistic Studies of the Photo-Fenton Reaction for the Degradation of Organic Pollutants - Jr., Amilcar Machulek; Quina, Frank H.; Gozzi, Fabio; Silva, Volnir O.; Friedrich, Leidi C.; Moraes, José E. F. (IntechOpen, 2012)
None